The cybernetic imagination of computational architecture. (March 2016) - Quin, Camilo Andrés Cifuentes
Since the publication in 1948 of Norbert Wiener's Cybernetics, this thought model has exerted a profound influence in contemporary knowledge. Such influence has been decisive for a paradigm shift in the profession of architecture and particularly for the rise of a computational perspective in architectural design. This article explores the link between the cybernetic paradigm and the conception of architectural objects as performative, responsive, intelligent, and sentient artifacts—the visions of buildings that have been central to the development of digital architecture since its early stages. This connection shows that the dominant visions of design problems associated with the development of a computational perspective in architecture have not been exclusively the result of the introduction of computer pragmatics in architectural design. On the contrary, following such scholars as Bruno Latour and Katherine Hayles, these developments must be considered as the result of a particular feedback process that includes technical aspects as well as the definition of design problems around an informational ontology and epistemology. The understanding of the intellectual foundations of digital architecture is crucial not only to promote a critical regard of its productions but to imagine scenarios for a viable cybernetic practice of computer-mediated architectural design.